Various Applications of Methods and Elements of Adaptive Optics - Sheldakova, Julia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume is focused on a wide range of topics, including adaptive optic components and tools, wavefront sensing, different control algorithms, astronomy, and propagation through turbulent and turbid media.